REGIONAL TOURISM AS A STRATEGIC SECTOR FOR PORTUGAL: SUN, SEA AND MUCH MORE - Portugal Duarte, António (Journal of the Geographical Institute “Jovan Cvijić” SASA, 2015)
For its overriding importance in employment, investment, and the development of other activities, tourism is presented as a priority strategic sector for Portugal. After many years during which Portugal’s tourism industry focused mainly on the “Sun and Sea” product, there is now more diversification in product offerings in the country, ranging from green and beach tourism to health and well-being tourism, incorporating along the spectrum, sports, cultural, and business tourism. This diversification, and subsequent promotion of supply has allowed the development of the sector both qualitatively and quantitatively, and the emergence of touristic activities in new regions has leveraged not only greater uniformity in the use of available resources, but also helped to avoid the adverse effects of seasonality so characteristic of traditional tourism based on the “Sun and Sea”.